Multicenter study of quality of life and its determinants in perimenopausal and postmenopausal women - Papakonstantinou, Aikaterini; Malliarou, Maria; Sarafis, Pavlos (International Conference on Business and Economics - Hellenic Open University, 2025)
Although menopause is a normal biological event, it does not cease to mark an important transition in women’s lives, with many physical and psychological changes that can have a catalytic effect on their quality of life. The purpose of this study was to evaluate the quality of life in menopausal women and its correlation with climacteric symptoms and self-esteem, as well as to identify those determinants that may be associated with quality of life. This was a cross-sectional observational study. The final sample consisted of 278 cases, aged 45-65 years. A demographic questionnaire and the UTIAN Quality of Life, GREEN climacteric symptoms and Rosenberg self-esteem scales were used. Menopausal symptoms and self-esteem, were found to have a statistically significant effect on the overall QoL scale (p<0.001). Regarding the various determinants, only better self-assessment of health, as well as support from the family and social environment were related to better QoL. On the contrary, overweight/obese women had worse overall QoL. However, other factors played an important prognostic role, such as smoking, being married, exercise and healthy diet, regular visits to the gynecologist for check-up, satisfaction with the financial and living standards, information from the scientific community about menopause. Regarding the ways menopause was managed, the percentages of women who modified their lifestyle (exercise, diet) were small. In conclusion, there is a need for health promotion programs to empower and thoroughly inform women about the consequences of menopause, treatment options, but also the importance of adopting a healthier lifestyle. JEL Classification: I10, I12, I18, I31 Keywords: menopause, climacteric symptoms, self-esteem, quality of life, hormone replacement therapy